Two-dimensional population balance modelling and validation of combined cooling and antisolvent crystallization of l-asparagine monohydrate. Issue 9 (14th February 2023) - Lenka, Maheswata; Bhoi, Stutee; Sarkar, Debasis
Abstract : Combining cooling and antisolvent modes of crystallization is advantageous as it may significantly improve the process performance. Abstract : Combining cooling and antisolvent modes of crystallization is advantageous as it may significantly improve the process performance. A set of experiments were conducted on combined cooling and antisolvent crystallization of l -asparagine monohydrate (LAM) in water/isopropanol mixture. Due to its size, the LAM crystals were represented by two characteristic dimensions (length and width) and a two-dimensional population balance equation (PBE) for the system was developed to predict the evolution of crystal size distribution (CSD). The measured solute concentration and size distribution data were used to estimate the nucleation and growth kinetics by solving the population balance model combining with a nonlinear optimization technique. The nucleation rate and birth rate were described by classical nucleation theory and BCF model, respectively. The high resolution finite volume discretization scheme with a flux limiter was used to solve the PBE for simulating the crystallization process. The estimated parameters predict the time evolution of concentration and CSD reasonably well for all the cases studied.